EFFORTS IN CONTROLLING COAL DUST HAZARDS IN THE STOCKPILE AREA OF A STEAM POWER PLANT (PLTU) - Alifiah Rizky Rosydah; Y. Denny Ardyanto Wahyudiono; Ahmad Imaduddin; Dani Nasirul Haqi; Meirina Ernawati (Journal of Vocational Health Studies, 2022)
Background: The movement of coal or other activities in the stockpile area of a steam power plant can create a coal dust hazard or commonly referred to as respirable dust. The smaller the particle size, the more harmful effects it can have on human health, such as bronchitis, decreased lung function, Chronic Obstructive Pulmonary Disease (COPD), Coal Worker's Pneumoconiosis (CWP), and other respiratory diseases. Purpose: To study the chemical hazards of the working environment of coal dust and the control efforts conducted in the stockpile area of a steam power plant company. Method: This research was descriptive observational with a cross-sectional study. The data were comprised of primary data collected from interviews and observations, and secondary data such as environmental measurement report and documentations owned by company. Result: The results of the measurement of coal dust hazard in the stockpile are were 0.007 mg/m3 and 0.063 mg/m3 for personal dust measurements. Some of the coal-dust-hazard control efforts performed by PT. POMI included the installation of a spray gun, a dust suppression system, reforestation, and ventilation setting. Further, OHS induction was conducted, together with safety talk, working hour regulations, toolbox meeting, training on the use of PPE, Medical Check Up (MCU), person authorization, preventive maintenance, and the use of PPE by workers. Conclusion: The measurement of the coal dust hazard in the stockpile area is below the threshold value which is 3 mg/m3 for respirable particles and 10 mg/m3 for inhalable particles. PT. POMI has done several preventive and control efforts towards coal dust hazard, and there were no health problems found in workers.